Development of Learning Modules Based on Local Wisdom of the Sasak Tribe in IPAS Subjects Chapter 6 Matter "My Indonesia is Rich in Culture" - Qoini, Zohratul Nita; Makki, Muhammad; Nurwahidah; Nisa, Khairun (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This study aims to produce a product in the form of a learning module based on local wisdom of the Sasak tribe in the subject of IPAS chapter 6 material "My indonesia is rich in culture" grade IVth SDN 3 Suranadi which is valid and practical. This type of research uses the type of development research (R&D) with the ADDIE research model (Analysis, Design, Development, Implementation, Evaluation). The data collection instruments used are material validation questionnaire, media validation questionnaire, student response questionnaire, and teacher response questionnaire. The results of this study indicate that the learning module based on the local wisdom of the Sasak tribe in the IPAS subject chapter 6 "My Indonesia is Rich in Culture" obtained a percentage value of 84.4% with a highly valid category by media experts and obtained a percentage value of 85.7% with a highly valid category by material experts. In the practicality test by students obtained a percentage value of 96.3% with a highly practical category and the practicality test by teachers obtained a percentage value of 97.5% with a highly practical category. Therefore, it can be concluded that based on the results of the research, the learning module based on the local wisdom of the Sasak tribe in the IPAS subject chapter 6 matter "My Indonesia is Rich in Culture" grade IV is declared valid and practical to use.